2019
DOI: 10.1016/j.physletb.2019.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a fine structure in e+e− → hadrons production at the nucleon-antinucleon threshold

Abstract: A study of hadron production at the nucleon-antinucleon threshold has been performed with the CMD-3 detector at the VEPP-2000 e + e − collider. The very fast rise with about 1 MeV width has been observed in the e + e − →

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…In the new detail scan the CMD-3 confirmed observed earlier [24] fast drop of the e + e − → 3(π + π − ) cross section at the NN production threshold as seen in Fig. 7 [25]. It was found that one more channel shows similar behaviour -e + e − → K + K − π + π − as seen in Fig.…”
Section: Other Hadronic Channelssupporting
confidence: 75%
See 1 more Smart Citation
“…In the new detail scan the CMD-3 confirmed observed earlier [24] fast drop of the e + e − → 3(π + π − ) cross section at the NN production threshold as seen in Fig. 7 [25]. It was found that one more channel shows similar behaviour -e + e − → K + K − π + π − as seen in Fig.…”
Section: Other Hadronic Channelssupporting
confidence: 75%
“…Cross section of e + e − → 3(π + π − ) process measured by CMD-3[25]. The solid line is a fit with empirical function.…”
mentioning
confidence: 99%
“…Generalized FF as a function of the four-momentum q 2 . The data are from CMD-3[23] (red stars), BaBar[16,21] (black circles), BESIII[19] (blue squares), and[18] (green triangles). They are shown together with the six-parameter fit from[22] compared to the fit from[20] (red dashed line).…”
mentioning
confidence: 99%
“…Space-like proton form factors have been measured with very high precision in many experiments [ 22 , 23 ]. In the time-like region, there have been a few measurements of G eff by DM2 [ 24 , 25 ], E760 [ 26 ], PS170 [ 27 ], FENICE [ 28 ], E835 [ 29 , 30 ], BaBar [ 31 , 32 ] and CMD-3 [ 33 , 34 ], but these have relatively poor precision and mutual agreement. For the | G E / G M | ratio, the measurements were rare and there is a long-time tension between PS170 and BaBar.…”
Section: Baryon Form Factor Measurements At Besiiimentioning
confidence: 99%